Delivery of pineal melatonin to the brain and SCN: role of canaliculi, cerebrospinal fluid, tanycytes and Virchow–Robin perivascular spaces - Reiter, Russel J.; Tan, Dun Xian; Kim, Seok Joong; Cruz, Maria Helena C. (Brain Structure and Function, 2014)
Historically, the direct release of pineal melatonin into the capillary bed within the gland has been accepted as the primary route of secretion. Herein, we propose that the major route of melatonin delivery to the brain is after its direct release into the cerebrospinal fluid (CSF) of the third ventricle (3V). Melatonin concentrations in the CSF are not only much higher than in the blood, also, there is a rapid nocturnal rise at darkness onset and precipitous decline of melatonin levels at the time of lights on. Because melatonin is a potent free radical scavenger and antioxidant, we surmise that the elevated CSF levels are necessary to combat the massive free radical damage that the brain would normally endure because of its high utilization of oxygen, the parent molecule of many toxic oxygen metabolites, i.e., free radicals. Additionally, the precise rhythm of CSF melatonin provides the master circadian clock, the suprachiasmatic nucleus, with highly accurate chronobiotic information regarding the duration of the dark period. We predict that the discharge of melatonin directly into the 3V is aided by a number of epithalamic structures that have heretofore been overlooked; these include interpinealocyte canaliculi and evaginations of the posterodorsal 3V that directly abut the pineal. Moreover, the presence of tanycytes in the pineal recess and/or a discontinuous ependymal lining in the pineal recess allows melatonin ready access to the CSF. From the ventricles melatonin enters the brain by diffusion and by transport through tanycytes. Melatonin-rich CSF also circulates through the aqueduct and eventually into the subarachnoid space. From the subarachnoid space surrounding the brain, melatonin penetrates into the deepest portions of the neural tissue via the Virchow–Robin perivascular spaces from where it diffuses into the neural parenchyma. Because of the high level of pineal-derived melatonin in the CSF, all portions of the brain are better shielded from oxidative stress resulting from toxic oxygen derivatives.